. Solve the following homogeneous differential equation: (x + 2y)dx − xdy = 0
"\\left( {x + 2y} \\right)dx - xdy = 0 \\Rightarrow \\frac{{dy}}{{dx}} = \\frac{{x + 2y}}{x} \\Rightarrow y' = 1 + 2\\frac{y}{x}"
Let
"\\frac{y}{x} = t \\Rightarrow y = tx \\Rightarrow y' = t'x + t"
Then
"t'x + t = 1 + 2t \\Rightarrow x\\frac{{dt}}{{dx}} = 1 + t \\Rightarrow \\frac{{dt}}{{1 + t}} = \\frac{{dx}}{x} \\Rightarrow \\ln (1 + t) = \\ln x + \\ln C \\Rightarrow 1 + t = Cx \\Rightarrow 1 + \\frac{y}{x} = Cx \\Rightarrow y = x\\left( {Cx - 1} \\right) \\Rightarrow y = C{x^2} - x"
Answer: "y = C{x^2} - x"
Comments
Leave a comment